2022
DOI: 10.3389/fnut.2022.852944
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mutations analyses of FTO (fat mass and obesity-associated gene) and their effects on FTO’s substrate binding implicated in obesity

Abstract: An excessive amount of fat deposition in the body leads to obesity which is a complex disease and poses a generic threat to human health. It increases the risk of various other diseases like diabetes, cardiovascular disease, and multiple types of cancer. Genomic studies have shown that the expression of the fat mass obesity (FTO) gene was highly altered and identified as one of the key biomarkers for obesity. This study has been undertaken to investigate the mutational profile of the FTO gene and elucidates it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…37 Its expression was identified as one of the key biomarkers for obesity. 38 The FTO genetic variant has been also linked to major markers of insulin resistance and inflammation, with an increased risk of type 2 diabetes. 39 Diabetes is a major risk factor for the development and progression of periodontal disease, 30,40 as well as obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Its expression was identified as one of the key biomarkers for obesity. 38 The FTO genetic variant has been also linked to major markers of insulin resistance and inflammation, with an increased risk of type 2 diabetes. 39 Diabetes is a major risk factor for the development and progression of periodontal disease, 30,40 as well as obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The FTO gene was found to be highly dysregulated and contributed to obesity 37 . Its expression was identified as one of the key biomarkers for obesity 38 . The FTO genetic variant has been also linked to major markers of insulin resistance and inflammation, with an increased risk of type 2 diabetes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This approach is possible with evolving in silico approaches that provide statistically significant results with visually vibrant and easy-to-understand data with a very low false discovery rate. Recently, Kumar et al, (2022) [ 16 ] displayed via in silico analysis the mutational profile of the FTO gene and explained how it affects protein structure and function. In detail, they analyzed the FTO gene's mutational profile and monitored the influence of nonsynonymous (missense) mutations on the structure, dynamics, conformation, and substrate binding of the FTO protein.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 As radical scavengers, flavonoids are capable of hampering the oxidation of lowdensity lipoprotein (LDL) and then exert their inhibitory action against atherosclerosis. 14 Through molecular docking and simulation studies, different flavonoids such as quercetin, exemestane, kaempferol, letrozole, rutin, 22 catechins, epicatechin, epigallocatechin and gallocatechin 10 are reported to have inhibitory interaction with FTO protein in the adipocytes, where they exert their anti-obesity effects through lipolytic mechanism by reducing adipogenesis and enhancing lipolysis. 10,22 Molecular docking studies have also reported the activity of other flavonoids such as flavonols, 23 apigenin, naringenin, 24 and taiwaniaquinoids 25 as anti-obesity agent targeting the FTO protein.…”
mentioning
confidence: 99%
“…14 Through molecular docking and simulation studies, different flavonoids such as quercetin, exemestane, kaempferol, letrozole, rutin, 22 catechins, epicatechin, epigallocatechin and gallocatechin 10 are reported to have inhibitory interaction with FTO protein in the adipocytes, where they exert their anti-obesity effects through lipolytic mechanism by reducing adipogenesis and enhancing lipolysis. 10,22 Molecular docking studies have also reported the activity of other flavonoids such as flavonols, 23 apigenin, naringenin, 24 and taiwaniaquinoids 25 as anti-obesity agent targeting the FTO protein. This study investigated the anti-obesity potentials of flavonoids including quercetin, epigallocatechin, pcoumarin, caffeic acid, naphthoresorcinol, gallic acid, and sinapic acid, isolated from methanol flavonoid-rich fraction of fresh lime juice (MFLJ) and ethylacetate flavonoid-rich fraction of honey (EAFH) via in silico approach.…”
mentioning
confidence: 99%